2018
DOI: 10.1016/j.artd.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid is associated with increased readmission and resource utilization after primary total knee arthroplasty: a propensity score–matched analysis

Abstract: BackgroundMedicaid payer status has been shown to affect resource utilization across multiple medical specialties. There is no large database assessment of Medicaid and resource utilization in primary total knee arthroplasty (TKA), which this study sets out to achieve.MethodsThe Nationwide Readmissions Database was used to identify patients who underwent TKA in 2013 and corresponding “Medicaid” or “non-Medicaid” payer statuses. Demographics, 15 individual comorbidities, readmission rates, length of stay, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Previous studies showed that Medicaid patients had higher rates of inpatient resource use, higher costs, and higher rates of readmission after hip or knee replacement than non-Medicaid patients. [12][13][14][15][16][17] However, research is lacking on PAC disparities after joint replacement surgery. This study contributes to the literature by demonstrating more intensive institutional PAC use but lower PAC quality and outcomes for dual-eligible patients relative to Medicare-only patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Medicaid patients had higher rates of inpatient resource use, higher costs, and higher rates of readmission after hip or knee replacement than non-Medicaid patients. [12][13][14][15][16][17] However, research is lacking on PAC disparities after joint replacement surgery. This study contributes to the literature by demonstrating more intensive institutional PAC use but lower PAC quality and outcomes for dual-eligible patients relative to Medicare-only patients.…”
Section: Discussionmentioning
confidence: 99%
“…It additionally allows for controlling of socioeconomic factors by reporting insurance status as well as zip code income quartile. Both factors that have been associated with outcomes [37][38][39], and the ability to control for these represents an important strength compared to other database studies. Also, readmissions can be tracked even if the readmission occurs at a different institution, therefore providing a higher capture rate for outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to explore the effect of the 3 major insurance types (Medicaid, Medicare, and commercial) on hospital LOS and 90-day global events in fast-track primary total hip and knee arthroplasty. Previous studies have stratified patients into Medicaid or non-Medicaid payer status or had relatively high mean LOS [8], [9], [10]. Browne et al [8] retrospectively reviewed 191,111 patients who underwent primary TJA between 2002 and 2011 using the Nationwide Inpatient Sample.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 studies dissected the effect of payer type on LOS into the 3 major insurance groups (Medicaid, Medicare, and commercial), but only in THA [5], [11]. Collectively, these studies found higher rates of in-hospital morbidity, prolonged LOS, and resource utilization among Medicaid and Medicare patients [5], [8], [9], [10], [11]. We are not aware of similar reports comparing the 3 major insurance groups in TKA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation